Панегіричне звеличення Йоасафа Кроковського - Сєдіна, Д. (Слово і Час, 2020)
У статті проаналізовано панегіричну поему, присвячену Йоасафові Кроковському, важливій постаті в українському культурному житті та в
українській православній Церкві XVII—XVIII ст. (він обіймав три найважливіші посади: ректор Києво-Могилянської колегії, архімандрит Києво-Печерського монастиря й митрополит). Поему було написано 1699
року, коли Кроковський був архімандритом Києво-Печерського монастиря. Головною метою поезії в той час уважали сприяння вихованню благочестивих людей і лояльних підданих, тому панегірик був одним із провідних жанрів у могилянських поетиках. І найкращим способом досягнення
цієї мети було зображення зразкових людських учинків, які би становили
варті наслідування взірці.Твір свідчить про вплив філософії гуманізму та
Відродження на українську літературу. The author analyzes a long and complex panegyric poem dedicated to Yoasaf Krokovskyi,
a key figure in Ukrainian cultural life and Orthodox Church of the late 17th — early 18th
centuries (he was elevated to the three prominent Orthodox ecclesiastical posts in the Hetmanate:
rector of the Kyiv Mohyla Collegium, archimandrite of the Kyivan Cave Monastery,
and metropolitan). The poem was written in 1699 when Krokovskyi held the post of
the Kyivan Cave Monastery archimandrite. Since the main goal of poetry at the time was
contributing to the education of pious men and loyal subjects, panegyric poetry was one of
the principal genres of Mohylanian poetics. Indeed, the best way to achieve this goal was to
represent exemplary human actions that would constitute models worthy of emulation. The
didactic function of praise was all the more effective when the characters being praised were
familiar to the students.
The analyzed poem is found in the 1699 manual of poetics “Hymettus extra Atticam”,
whose author was Yosyf Turoboiskyi, a Mohylanian professor who steadily entered the history
of Russian culture due to his celebratory works in honor of Peter I, while in Ukrainian
literature he is almost unknown. The central theme of the analyzed poem, written on
the occasion of Krokovskyi’s birthday, is a virtue of the addressee and wisdom that inspires
him. These themes reveal, on one side, the author’s intention to insert the personality of
archimandrite and future metropolitan into what N. Pylypiuk saw as a project, initiated in
the 1690s, of portraying Mazepa and Yasynskyi with visual and textual means as protectors
and benefactors of Wisdom’s abode, that is the Collegium and St. Sophia. On the other,
they reflect the idea of wisdom as it was characterized by the Renaissance; it is mirrored in
the Erasmian definition of wisdom as “virtus cum eruditione liberali conjuncta”. This fact,
expanding the topic of epic poetry to all activities related to the intellect, reflects the Renaissance
approach to the ‘heroicum carmen’ and testifies to the influence of Humanism and
Renaissance on the Ukrainian literature.